SISTEM INFORMASI PEMBELIAN DAN PENJUALAN PADA UMKM YOGHURT MYOO - Upayarto, Budi; Yulianto, Hildan Zaelani (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
The study aims to analyze, design, implement, and test the purchasing and sales information system at Yoghurt Myoo MSMEs. The research method used is a qualitative descriptive method with data collection using observation, interviews, documentation, and literature studies. Waterfall is used to develope the system. The results of the study state that the information system application has fulfilled the functional needs according to the design made. The resulting information system can provide solutions to existing problems at Yoghurt Myoo MSMEs, namely the system can make recording easier and report generation more efficient. The programming language used is a Microsoft Excel Basic For Application-based system. Based on the results of the developer's test, it states that the purchasing and sales application created has run according to the design objectives and has met the expected criteria, while the test results from the user side show an average value of 77% which means it has very good criteria and is suitable for use by users.